Predictive value of C-reactive protein and clinically relevant baseline variables in sarcoidosis - McDonnell, Melissa J.; Saleem, Mohammed I.; Wall, Deidre; Gilmartin, J. J.; Rutherford, R. M.; O'Regan, Anthony (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: This study aims to examine the predictive and prognostic implications of C-reactive protein (CRP) and clinically relevant baseline variables in determining treatment indication and disease progression in a large clinical cohort of patients with stable sarcoidosis. Methods: A retrospective observational study of 328 sarcoidosis patients attending a regional tertiary referral centre over a 26-year period was performed. Clinical, biochemical, radiological and physiological data were analysed according to a clinically relevant dichotomous cutpoint of CRP. Multiple models of logistic regression were used to determine independent predictors of outcome as defined by indication for treatment with corticosteroids, radiological deterioration and physiological progression. Results: 328/409 (80.2%) sarcoidosis patients had baseline serum CRP measured and were suitable for inclusion. Baseline CRP was elevated in 154 (47%). 178 (54.3%) were prescribed corticosteroid treatment during the disease course. Physiological deterioration was demonstrated in 48 (14.6%) patients and radiological progression in 59 (17.9%) patients. High baseline CRP was strongly associated with Lofgren’s syndrome (p=